2003
DOI: 10.1038/sj.ijo.0802379
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in obese outpatients losing weight with very-low-energy diet and behaviour modification—a 2-y follow-up study

Abstract: OBJECTIVE:To study health-related quality of life (HRQL) in a clinically selected sample of obese outpatients. DESIGN: A single-strand before and after study with 2-y follow-up after treatment comprising 10 weeks on very-low-energy diet (VLED) and 4 months of behaviour modification in groups. SUBJECTS: A total of 126 (mean (s.d.) age 48.2 (11.1) y and body mass index 42.8 (6.2) kg/m 2 obese patients (63% women) referred for treatment in an obesity clinic. MEASUREMENTS: Weight and HRQL using questionnaires (RAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 42 publications
5
21
1
Order By: Relevance
“…Very few studies have examined this relationship for adults with T2DM [19], and no study has been done on a large population-based sample of T2DM. The present study found a similar association of weight loss and improvement in HRQOL as other studies among the general population [14, 16–18]. With this evidence that weight loss is associated with improved HRQOL among individuals with T2DM, it is important to determine if the improved HRQOL along with the weight loss will assist T2DM patients to better manage their diabetes (possibly improve medication adherence and glucose monitoring) and control their glucose levels.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Very few studies have examined this relationship for adults with T2DM [19], and no study has been done on a large population-based sample of T2DM. The present study found a similar association of weight loss and improvement in HRQOL as other studies among the general population [14, 16–18]. With this evidence that weight loss is associated with improved HRQOL among individuals with T2DM, it is important to determine if the improved HRQOL along with the weight loss will assist T2DM patients to better manage their diabetes (possibly improve medication adherence and glucose monitoring) and control their glucose levels.…”
Section: Discussionsupporting
confidence: 86%
“…Cross-sectional studies among the general population have shown a clear inverse relationship with baseline weight or BMI and health-related quality of life (HRQOL) [1113]. Studies examining the change in weight over time and HRQOL found that weight gain led to a reduction in HRQOL [14, 15], and in general, weight loss (5%–10%) was associated with significant improvement in HRQOL, typically in physical functioning and bodily pain [14, 16–18]. However, only one study examined this association among individuals with T2DM [19], where the results indicated that patients with diabetes who lost >5% of their weight during the clinical trial had improved their HRQOL scores.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, changes in diet 4-11 and weight status are associated with changes in quality of life: weight gain is associated with lower measures of quality of life while weight loss is associated with improvements. 4,12-20 Because of its focus on dietary change and its size, the dietary modification (DM) trial of the Women’s Health Initiative (WHI) may be able to contribute to the question of whether or not making healthy diet changes is associated with improved HRQoL, both overall and within subgroups of women. The DM trial in the WHI was a randomized controlled trial designed to test the hypothesis that a reduction of fat intake to 20 percent of the total daily calories and an increase in the intake of fruit, vegetables, and whole grains would reduce the risk of breast cancer and of colorectal cancer and, as a secondary outcome, the risk of heart disease in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Proponents of rapid weight loss [18] have favored strong reductions arguing that a greater initial weight loss was predictive of more long-term weight loss [19]. Proponents of a modest weight reduction have argued that achieving between 5 and 10% of weight reduction carried significant benefits regarding blood pressure, serum lipids, coronary risks, etc.…”
Section: Introductionmentioning
confidence: 99%